2013
DOI: 10.1074/jbc.m113.450403
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Bre1p, an E3 Ligase for Histone H2B Ubiquitylation, in Regulation of RNA Polymerase II Association with Active Genes and Transcription in Vivo

Abstract: Background: Bre1p is required for H2B ubiquitylation that promotes RNA polymerase II association with active genes, and hence transcription. Results: The RING domain of Bre1p facilitates, but a non-RING domain represses, transcription and RNA polymerase II association with active genes. Conclusion: Bre1p has a dominant-negative role in addition to its well known stimulatory function in transcription. Significance: This study unravels a hidden role of Bre1p in transcriptional regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 57 publications
5
22
0
Order By: Relevance
“…Likewise, the loss of Paf1p impairs sense transcription of ACT1 (Fig. 6I and J), consistent with previous studies (29). Thus, our results demonstrate that Paf1p facilitates GAL10 antisense transcription.…”
Section: Figsupporting
confidence: 81%
See 3 more Smart Citations
“…Likewise, the loss of Paf1p impairs sense transcription of ACT1 (Fig. 6I and J), consistent with previous studies (29). Thus, our results demonstrate that Paf1p facilitates GAL10 antisense transcription.…”
Section: Figsupporting
confidence: 81%
“…Likewise, Rad6p promoted sense transcription of ACT1 (Fig. 6A and B), consistent with previous studies (26,29). As a loading control, we showed that the 18S rRNA level was not altered in the ⌬rad6 strain (Fig.…”
Section: Figsupporting
confidence: 79%
See 2 more Smart Citations
“…During transcriptional elongation, Spt16 promotes chromatin reassembly in the wake of RNA polymerase II to maintain the fidelity of transcriptional elongation (9)(10)(11). Likewise, histone H2B ubiquitylation is also involved in transcriptional elongation via enhancement of chromatin reassembly in the wake of elongating RNA polymerase II (10,(39)(40)(41). Moreover, histone H2B ubiquitylation (or Rad6/Bre1) and Spt16 interact functionally to promote chromatin reassembly and transcriptional elongation (10).…”
Section: Resultsmentioning
confidence: 99%